2020
DOI: 10.7759/cureus.12228
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Complications in Adult Tracheostomy

Abstract: Objective Tracheostomy is one of the oldest operations for the management of airway obstruction. With time, indications expanded to prolonged mechanical ventilation, and currently, the majority of tracheostomies are done for this reason. There are several techniques used in a tracheostomy procedure, depending on surgeon preference. Immediate complications such as bleeding, pneumothorax, pneumomediastinum, airway fire, and posterior tracheal wall perforation with esophageal injury are rare, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Based on the present results, we recommend that surgeons should pay careful attention to complications during ST under local anaesthesia and in airway emergencies. Awake tracheostomy is 6.2 times more likely to result in pneumothorax or pneumomediastinum than general tracheostomy 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the present results, we recommend that surgeons should pay careful attention to complications during ST under local anaesthesia and in airway emergencies. Awake tracheostomy is 6.2 times more likely to result in pneumothorax or pneumomediastinum than general tracheostomy 5 …”
Section: Discussionmentioning
confidence: 99%
“…Awake tracheostomy is 6.2 times more likely to result in pneumothorax or pneumomediastinum than general tracheostomy. 5 Patients undergoing awake tracheostomy often breathe spontaneously after tracheostomy and are prone to the cough reflex due to the presence of a tracheal cannula, which may result in subcutaneous emphysema. Particularly, in airway emergencies, the risk of subcutaneous emphysema may have been increased because securing the airway is a top priority, despite the consideration of safety.…”
Section: Ta B L E 1 Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important complications of PDT is posterior wall perforation with esophageal injury. [ 16 ] Although rare in experienced hands, bronchoscopy guidance is the gold standard to avoid this complication. Balaban et al[ 17 ] reported in their case series that they successfully completed the PDT procedure under US guidance and accompanied by bronchoscopy in three patients, one of whom was operated for aortic dissection, one patient with trauma and one with hypoxic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Postoperative complications of ST are rare, and the early and late postoperative complication rates are 5.6% and 7.1%, respectively. 3 Obesity and awake tracheostomy are major risk factors for postoperative complications of ST. 4,5 Further, four or more comorbidities are reported to increase the risk of postoperative bleeding, which is the most frequent early complication of ST. 3,6 Additionally, ST is sometimes necessary for patients undergoing continued antithrombotic therapy (CAT), which can exacerbate the risk of bleeding. However, there is a dearth of data regarding ST under CAT.…”
Section: Introductionmentioning
confidence: 99%